Rethinking Freight Transport: A Systemic Policy Model for Curbing Over Dimension Over Load (ODOL) in Indonesia - Edi Abdurachman; Abdullah Ade Suryobuwono; Sita Aniisah Sholihah; Lis Lesmini (Siber Journal of Transportation and Logistics, 2025)
The persistent challenge of Over Dimension Over Load (ODOL) violations in Indonesia's freight transport system poses critical threats to road infrastructure integrity, traffic safety, and economic efficiency. Despite regulatory frameworks established through Ministry of Transportation directives, enforcement remains fragmented, and compliance rates remain alarmingly low. This study develops an integrated multimodal transportation policy model employing Soft Systems Methodology (SSM) to address systemic ODOL violations through coordinated stakeholder engagement, technology-enabled enforcement, and strategic modal integration. Drawing on comprehensive analysis of 100+ peer-reviewed publications (2020-2025), international regulatory standards, and empirical enforcement data, this research constructs a holistic framework that transcends traditional command-and-control approaches. The proposed model integrates Weigh-In-Motion (WIM) technology deployment, port-gate digital integration systems, progressive sanction mechanisms calibrated to infrastructure damage externalities, and multimodal freight corridor development. Through SSM's seven-stage methodology, the study maps complex stakeholder interactions among government agencies, transport operators, infrastructure managers, and enforcement authorities, revealing systemic bottlenecks and leverage points for policy intervention. Empirical evidence from Abu Dhabi demonstrates 61% overload prevalence in unregulated environments, while Indonesian enforcement unit performance evaluations expose critical gaps in inter-agency coordination and enforcement capacity. The research proposes a phased nationwide implementation strategy encompassing governance architecture establishment, targeted enforcement pilots in high-risk corridors, sanction calibration linked to quantified road damage costs, and complementary modal shift incentives. This SSM-informed policy model offers actionable pathways for Indonesia to achieve Zero ODOL objectives while maintaining freight system efficiency and stakeholder viability, contributing theoretical advancement in systems-based transportation governance and practical frameworks for developing-country freight policy reform.